Multimodal Treatment of Hepatic Metastasis in the Form of a Bile Duct Tumor Thrombus from Pancreatic Acinar Cell Carcinoma: Case Report of Successful Resection after Chemoradiation Therapy - Kittaka, Hirotada (S. Karger AG, 2012)
Pancreatic acinar cell carcinoma (ACC) is a rare tumor, and its pathophysiology has not been well understood. Treatment strategies for hepatic metastasis originating from ACC remain controversial. We report the case of a 66-year-old woman who had undergone total pancreatectomy from ACC 7 years prior to clinical presentation. Contrast-enhanced computed tomography imaging revealed a tumorous lesion measuring 7 cm in length and 1 cm in diameter and extending along the intrahepatic bile duct (B6), which showed mild enhancement in the early phase and modest washout in the late phase. This lesion was diagnosed as hepatic metastasis primarily in the form of a bile duct tumor thrombus originating from the prior ACC by the pathological evaluation of the fine needle biopsy specimen. The patient underwent preoperative gemcitabine-based chemoradiation therapy followed by subsequent surgical resection, which included subsegmentectomy (S6) of the liver and complete removal of the bile duct tumor thrombus. The patient has had no recurrence during the past 8 months since her last surgery. Multimodal treatment including preoperative chemoradiation therapy might be beneficial especially for marginally resectable cases of ACC.